2008
DOI: 10.1007/s00330-008-1098-3
|View full text |Cite
|
Sign up to set email alerts
|

Do clinicians read our reports? Integrating the radiology information system with the electronic patient record: experiences from the first 2 years

Abstract: This study aimed to determine how clinicians adapted to and utilized new routines for accessing radiology reports after the integration of an electronic patient record (EPR) with a radiology information system (RIS). Activity-related data describing the availability and receipt of radiology reports were collected from the EPR and the RIS over a period of 2 years. Twelve percent of the final radiology reports had not been opened 4 weeks after they had been entered into the EPR. For opened reports, the median ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…These systems are evolving to meet people's needs by implementing larger networks, allowing patient access and integration of ever more items of patient data [8]. Although great advances have been made over the years, on-demand access to clinical information is still inadequate in many settings, contributing to duplication of effort, excess costs, adverse events, reduced efficiency [9] and inability to take full advantage of existing IS [10]. Although it is widely accepted that full access to integrated electronic patient records and instant access to up-to-date medical knowledge significantly reduces faulty decision making resulting from lack of information [5,11,12], there is still very little evidence that life-long EHR improve patient care [13].…”
Section: Introductionmentioning
confidence: 99%
“…These systems are evolving to meet people's needs by implementing larger networks, allowing patient access and integration of ever more items of patient data [8]. Although great advances have been made over the years, on-demand access to clinical information is still inadequate in many settings, contributing to duplication of effort, excess costs, adverse events, reduced efficiency [9] and inability to take full advantage of existing IS [10]. Although it is widely accepted that full access to integrated electronic patient records and instant access to up-to-date medical knowledge significantly reduces faulty decision making resulting from lack of information [5,11,12], there is still very little evidence that life-long EHR improve patient care [13].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of the ICT introduction [11,12] we found a RTAT reduction from 13.4 to 2.7 hours for preliminary, and from 22.6 to 15.1 hours for final reports. We also observed faster and more comprehensive clinical access to the results of diagnostic imaging after the introduction of RIS and PACS, and the integration of these with the EMR system.…”
Section: Discussionmentioning
confidence: 54%
“…In a study of clinicians' use of the reports in the EMR, we observed that clinicians read reports soon after they were available [12]. The median time from a preliminary report becoming available in the EMR until it was opened was 0.8 hours for Computed Tomography (CT) reports, and 1.1 hours for Computed Radiography (CR) reports.…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that the radiologist has a responsibility to patient care 17 and although they are expected to call with urgent findings, the definition of urgent is open to interpretation. Studies have also shown that many reports are never read 4–6,18,19 and so important but non‐urgent findings that are not verbally notified may go unmanaged by the referring doctor.…”
Section: Discussionmentioning
confidence: 99%